2019
DOI: 10.1097/prs.0000000000005956
|View full text |Cite
|
Sign up to set email alerts
|

Volumetric Analysis in Autologous Fat Grafting to the Foot

Abstract: Background: Pedal fat grafting is a safe, minimally invasive approach to treat pedal fat pad atrophy. Prior randomized controlled trials demonstrate that the fat as measured directly under the metatarsal heads disappears between 2 and 6 months after fat grafting, despite patients having relief for 2 years. The authors aim to use magnetic resonance imaging to further assess three-dimensional volume of fat in the foot after autologous fat grafting to help explain the mechanism for improved pain. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 18 publications
1
9
0
Order By: Relevance
“…The technique for fat injection utilized the Coleman method and is described in our previous reports on foot fat grafting. 2 , 3 There were no differences between the intervention and control groups in our previous studies.…”
Section: Methodsmentioning
confidence: 66%
See 2 more Smart Citations
“…The technique for fat injection utilized the Coleman method and is described in our previous reports on foot fat grafting. 2 , 3 There were no differences between the intervention and control groups in our previous studies.…”
Section: Methodsmentioning
confidence: 66%
“… 2 , 5 The thickness of the fat pad is initially increased and then returns to baseline with long-term increases in the volume of the fat pad distributed around the metatarsal head. 3 Other benefits of pedal autologous fat grafting to various areas of the foot have been shown, including improvement of skin quality, treating adult flatfoot deformity, and decreasing the frequency of diabetic foot wounds. 7-9 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…14 PFG has been successfully implemented as treatment for a number of pedal conditions such as diabetic foot ulcers, pedal fat pad atrophy, thromboangiitis obliterans, plantar fibromatosis, and plantar osteochondromas. 4,[15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] Although it has be shown that grafted lipoaspirate redistributes over time in the plantar foot surface, it retains its supportive and analgesic function. 22 Considering this, the investigators expected that PFG holds potential therapeutic benefit to treat conditions, which results in elevated localized pedal pressure by providing a mechanism to dissipate said elevated pressure.…”
Section: Introductionmentioning
confidence: 99%
“…4 Autologous fat transplantation (AFT) has become a widely used technique in reconstructive plastic surgery. 5 It has the advantages of available tissue sources and low immunogenicity. However, transplanted adipose tissue cannot tolerate hypoxia, easily liquefies, has a low survival rate, and has difficulty reconstructing the blood circulation.…”
mentioning
confidence: 99%